STUDY OF FUND ALLOCATION FOR MAKASSAR CITY DRAINAGE CHANNEL MAINTENANCE: Case Study Bumi Tamalanrea Permai District. Tamalanrea - Hanafi Ashad; Abd Karim Hadi; Suryanti Adnan (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2020)
Bumi Tamalanrea Permai Housing is a housing development that began to be developed in 1990. Many lands that were originally water catchment areas have now been converted into residential, industrial, office and trade areas. During the rainy season with maximum rainfall in the Tamalanrea Permai Earth Area (BTP), extensive inundation occurs. This condition is strongly influenced by the capacity of the channel, how much sedimentation is and how much the maintenance costs for the existing drainage channel are. The objectives of this research are 1) To know the optimization of drainage channel capacity in the BTP Tamalanrea area based on hydrological analysis and hydraulics analysis. 2) Knowing the capacity of the drainage channel due to sedimentation. 3) Knowing the financing of drainage channel maintenance. The research method used is survey method, case study which contains a review of real conditions through field observations accompanied by analysis based on existing methods or formulas. The research design includes site survey, primary and secondary data collection, data analysis and design of culvert drainage dimensions based on hydrological and hydraulic analysis. The research area is divided into 4 (four) segments. The results show that 1) Optimization of drainage channel capacity based on hydrological and hydraulic analysis where the existing discharge must be greater than the design discharge (Qeks > Qrenc) has met, the results show that each segment shows Qeks > Qrenc which means the drainage is functioning and needs maintenance. 2) The presence of sedimentation causes the channel capacity to be smaller, so dredging must be carried out throughout the channel. 3) Based on all the results of the analysis and calculations carried out, the amount of costs required for maintenance activities is obtained by referring to the applicable regulations.